The theory, methods and application of managing digital supply chains - Mubarik, Muhammad Shujaat; Khan, Sharfuddin Ahmed (Emerald Publishing Limited, 2024)
Digital supply chain management (DSCM) is emerging as one of the key innovative strategies ready to transform how supply chains are managed. By enabling a faster and more cost-efficient delivery of products, improving products' traceability, enhancing coordination between supply chain entities, and helping with access to financing, DSCM is a powerful tool to address the supply chain issues of sustainability, traceability, verifiability and resilience. Muhammad Shujaat Mubarik and Sharfuddin Ahmed Khan provide a comprehensive explanation of the digital technologies driving supply chain management. Detailing the diverse aspects of digitalization in supply chain management, Digital Supply Chain Management helps business managers harness the cutting edge, guiding those early in their careers who seek a challenging new path whilst informing top-level managers who have their eye on the future.